Annex II – Cosine Similarity (Clean) Patent Dataset of US Domestic Filings - Oldham, Paul; Kim, Brian; Chiarolla, Claudio (2024)
Annex II – Cosine Similarity (Clean) Patent Dataset of US Domestic Filings